Impact of the DASH Diet on Intestinal Permeability and Inflammation Markers. (29th May 2020) - Lin, Pao-Hwa; Vliet, Stephan van; Lin, Chung-Yon; Svetkey, Laura; Tyson, Crystal; Scialla, Julia
Abstract: Objectives: The DASH (Dietary Approaches to Stop Hypertension) diet consistently reduces blood pressure (BP), but the mechanism remains unclear. Emerging evidence suggests that intestinal dysbiosis leading to increased intestinal permeability (IP) and inflammation may contribute to elevated BP. Using data collected from a pilot controlled feeding study (DASH-Mechanism) designed to explore the mechanisms of the BP-lowering of DASH, we examined the impact of DASH on IP and inflammatory markers. Methods: Randomized controlled feeding study where participants consumed a typical American diet for one week then were randomized to either continue the typical diet (control) or the DASH diet for two weeks. Data were collected at the end of the first week (baseline) and after two weeks of randomized feeding. Sera were analyzed for the IP marker-zonulin and for inflammatory markers hsCRP, IFN-g, IL-6 and TNF-a. Multivariate models were used to examine the effect of diet on the aforementioned biomarkers and the association of the change in biomarkers with change in BP. Results: Twenty unmedicated participants with stage 1 hypertension completed the study. Sera for this analysis were available for 18 participants (9 in control and 9 in DASH; Race: 5 Whites, 12 Blacks and 1 other; systolic/diastolic BP:140.1 ± 12.3/86.8 ± 14.2 mmHg). DASH diet significantly reduced SBP/DBP (−10.3 ± 11.7/−10.9 ± 5.9 vs 3.9 ± 6.6/3.6 ± 10.5 mmHg in control, P < 0.01 for both). There was a non-significant reduction in zonulin with DASH (Control: −1.97 ± 8.70 ng/ml; DASH: −5.81 ± 10.49 ng/ml), and a significant positive association between change in zonulin from baseline and change in both SBP ( P = 0.03) and DBP ( P = 0.05). Controlling for collinearity, multivariate linear model showed that change in zonulin, diet and age (for DBP only) (all P < 0.05) affect change in BP significantly (overall model: SBP P = 0.015 and DBP P = 0.022). Changes in inflammation markers did not differ between arms and none was associated with change in BP. Conclusions: Our findings suggest that the DASH diet may improve IP and such impact may be related to the BP lowering effect of DASH. Multivariate models also suggest independent effect of diet and zonulin on BP further implicates the potential role of IP in BP regulation. Investigation of the effect of DASH on the microbiota is warranted. Funding Sources: AHA.